Rancang Bangun Alat Pengukur Suhu Badan Tanpa Kontak Berbasis Arduino dengan Modul Inframerah dan Bluetooth - Arief Hendra Saptadi (MEDIA ELEKTRIKA, 2022)
The measurement of body temperature is necessary to prevent the spread of Covid-19. However, it must be conducted without any physical contact. This study aims to help users measure body temperature more quickly and accurately to detect Covid-19 suspects at a safe distance. The monitoring processes use the HC-05 bluetooth module and an application made with the MIT App Inventor is installed on an Android smartphone. This experiment uses an Arduino Uno with MLX90614 infrared temperature sensor, 16x2 LCD for text display, a buzzer as a warning alarm if the temperature is over 38ºC, and a tripod slot. The test conducted for MLX90614 sensor involved temperature measurement for a heated tap water object and three participants. The results indicated that the instrument can measure temperature with an accuracy of 98.63% to 99.55% through an effective distance of 5 cm. The designed software ran well on several versions of Android devices. Bluetooth connection test results in a maximum distance of 20 m with an obstacle and 25 m without an obstacle. A one-time battery endurance test is also carried out, which shows that the device can run for 165 minutes, while the bluetooth module is able to transmit the data to smartphone for 210 minutes.